2006
DOI: 10.1002/lt.20644
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of endoscopic treatment of biliary strictures after liver transplantation

Abstract: 19 patients (3.7%). Long-term success was observed in 77% of patients with AS. In patients with NAS, partial long-term responses could be achieved in 63% of patients. Five patients (6.2%) required a percutaneous and 6 (7.4%) patients a surgical approach.In conclusion, the long-term outcome for patients with post-liver transplant biliary strictures after endoscopic treatment is excellent, especially for patients with AS. Development of NAS reduces graft but not patient survival after endoscopic therapy. Liver T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
204
2
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(229 citation statements)
references
References 31 publications
16
204
2
7
Order By: Relevance
“…3 Donation after circulatory death (DCD) has been identified as a major risk factor for the development of ITBL in recipients, with the incidence rising up to 30%. 2 It is thought that the prolonged period of warm ischemia in DCD underlies the unrepairable injury to the biliary tree that predisposes patients to ITBL.…”
Section: See Article On Page 673mentioning
confidence: 99%
“…3 Donation after circulatory death (DCD) has been identified as a major risk factor for the development of ITBL in recipients, with the incidence rising up to 30%. 2 It is thought that the prolonged period of warm ischemia in DCD underlies the unrepairable injury to the biliary tree that predisposes patients to ITBL.…”
Section: See Article On Page 673mentioning
confidence: 99%
“…The incidence is greatest in the first 5 to 8 months (range, 1 to 36 months) (Gondolesi et al, 2004;Yazumi & Chiba, 2005;Kasahara et al, 2006). Recently, it has been suggested that prevalence continues to increase with time after transplantation , and that NAS presents earlier than AS, with mean time 3.3-5.9 months (Graziadei et al, 2006;Guichelaar et al, 2003). Moreover, NAS secondary to ischemic causes was shown to present within 1 year of the transplant, whereas the occurrence after 1 year was more often secondary to immunological causes .…”
Section: Biliary Stricturesmentioning
confidence: 99%
“…Hepatic angiography may be indicated if hepatic vascular abnormality was suspected (Thuluvath et al, 2005). US may have low sensitivity (close to 50%) to detect biliary dilatation in patients who received transplantation (Graziadei et al, 2006;Zoepf et al, 2005) and not accurate enough to diagnose or localize biliary strictures either because the true diameter of cast filled bile ducts could not be properly determined, acute obstruction may not result in a prompt dilatation of the prestenotic bile ducts (Zoepf et al, 2005) or because dilatation of the biliary system in allografts may develop slower (Shastri et al, 2007). Different studies reported variable results for helical computed tomography and magnetic resonance imaging.…”
Section: Value Of Radiological Modalities In Diagnosis Of Biliary Strmentioning
confidence: 99%
See 2 more Smart Citations